Pengaruh Kompetensi terhadap Kinerja Dosen Penddikan Agama Islam pada Universitas-Universitas di Padang - Akbar Akbar (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This research is motivated by the phenomenon related to PAI lecturer performance that is not optimal yet. The government has issued policies to improve the quality of lecturers as an effort to improve the quality of education through the improvement of welfare. However, conditions in the field show that some lecturers who have received the professional allowance have not shown any significant performance improvement. Some lecturers who have very good competence sometimes not followed by high performance, this is reflected from the results of the lecturer's performance.The purpose of this research are: (1) to know the level of competence and performance of lecturers of PAI in Padang city (2) to analyze efforts to improve the performance of PAI lecturers in Padang city (3) to find the level of competence influence on PAI lecturer performance in Padang city.This research is a quantitative type with survey method and correlational approach. The population is PAI lecturers at state universities in the city of Padang totaling 30 people. The sampling technique is total sampling. Data collection techniques used were the dissemination of questionnaires, documentation and literature study. While the data analysis technique used is the normality test Kolmogorof Smirnov method. Test validity using Product Moment Pearson correlation formula. Test reliability using Alpha Cronbach and processing analysis using SPSS version 15.The research findings are: (1) the actual condition of PAI lecturer competence in public universities in Padang city is generally quite good (TCR = 3,93 / 5,00 or = 76,98%) whereas actual condition of teaching performance of lecturer PAI lecturers at state universities in Padang city were in good condition (TCR = 3.81 / 5.00 or = 69.64 %). (2) The efforts to improve the performance of PAI lecturers according to the authors include: Planning the development of lecturer's performance, organizing lecturer performance assessment, conducting lecturer performance assessment with sustainability, supervising the performance of lecturers as well as following up the results of lecturer performance assessment. (3) there is a significant positive correlation between lecturer competence and lecturer performance of 22,3 %, meaning competence contribute to lecturer performance.Suggested to the lecturers of PAI to improve the competence to produce performance as expected. The various parties who have responsibility to improve the performance of lecturers are expected to give attention to the increased competence of PAI lecturers in order to give a significant influence in order to improve the quality of national education.